2022
DOI: 10.48550/arxiv.2203.11789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HD 133729: A blue large-amplitude pulsator in orbit around a main-sequence B-type star

A. Pigulski,
K. Kotysz,
P. A. Kolaczek-Szymanski

Abstract: Blue large-amplitude pulsators (BLAPs) form a small group of hot objects pulsating in a fundamental radial mode with periods of the order of 30 minutes. Proposed evolutionary scenarios explain them as evolved low-mass stars: either ∼0.3 M ⊙ shell-hydrogen-burning objects with a degenerated helium core, or more massive (0.5 -0.8) M ⊙ core-helium-burning stars, or ∼0.7 M ⊙ surviving companions of type Ia supernovae. Therefore, their origin remains to be established. Using data from Transiting Exoplanet Survey Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…However, one object worthy of attention in Table 1 is HD 133729. Pigulski et al (2022) reported a BLAP orbiting the main-sequence B-type star HD 133729 on an orbital period of 23.08433 d. The pulsation period of this BLAP is 32.37 min, with an amplitude 0.21 mag and a rate of period change of −11.5×10 −7 yr −1 , which is consistent with that of known BLAPs. The BLAP nature of the companion to HD 133729 was previously missed due to the dilution of the observed amplitude by the brighter primary.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, one object worthy of attention in Table 1 is HD 133729. Pigulski et al (2022) reported a BLAP orbiting the main-sequence B-type star HD 133729 on an orbital period of 23.08433 d. The pulsation period of this BLAP is 32.37 min, with an amplitude 0.21 mag and a rate of period change of −11.5×10 −7 yr −1 , which is consistent with that of known BLAPs. The BLAP nature of the companion to HD 133729 was previously missed due to the dilution of the observed amplitude by the brighter primary.…”
Section: Introductionsupporting
confidence: 77%
“…Except for HD 133729 (Pigulski et al 2022), no evidence for companion stars has been found in BLAPs so far (Pietrukowicz et al 2017;Kupfer et al 2015;Ramsay 2018;McWhirter et al 2020). This however does not necessarily imply that BLAPs are single stars.…”
Section: Formation Channel(s)mentioning
confidence: 95%
See 1 more Smart Citation
“…The shaded area indicates the approximate range of the gap between classical and high-gravity BLAPs. The new BLAP, HD 133729 [11], was not included here because its pulsation amplitude was not obtained directly from light curves.…”
mentioning
confidence: 99%
“…Rate of period change. BLAPs are believed to stem from either heliumcore pre-white-dwarfs (pre-WDs) or core helium-burning (CHeB) subdwarfs [1,2,[4][5][6]11], since stars formed from these two channels cover the BLAP region in the Hertzsprung-Russell (HR) diagram. The pre-WDs usually contract with the cooling process while the CHeB stars will burn helium steadily on nuclear timescales.…”
mentioning
confidence: 99%